(untitled) (Advancements in Homeopathic Research, 2022)
Down syndrome is a genetic disorder involving trisomy of chromosome 21, causing developmental and intellectual delays in children. Early intervention with a team of therapists and special educators can help in managing a case of Down syndrome. Homeopathy proved to be useful in managing incurable diseases like it. But, in case of a child, lack of subjective symptoms emerges like a barrier in selection of similimum. Keynote prescription is one such method of choice in such cases. A male, infant of age 11 months reported with complaints of recurrent coryza and delayed milestones. He had been diagnosed as suffering from Down syndrome with Hypothyroidism. Calcareacarbonica was prescribed which showed very good results in this case justifying the effectiveness of homeopathy in such challenging cases.